2021
DOI: 10.3389/fmolb.2021.706039
|View full text |Cite
|
Sign up to set email alerts
|

The Central Role of Redox-Regulated Switch Proteins in Bacteria

Abstract: Bacteria possess the ability to adapt to changing environments. To enable this, cells use reversible post-translational modifications on key proteins to modulate their behavior, metabolism, defense mechanisms and adaptation of bacteria to stress. In this review, we focus on bacterial protein switches that are activated during exposure to oxidative stress. Such protein switches are triggered by either exogenous reactive oxygen species (ROS) or endogenous ROS generated as by-products of the aerobic lifestyle. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 115 publications
0
4
0
Order By: Relevance
“…Since FLR7 affects rhizosphere oxygen levels, we further analyzed genes related to aerobic and anaerobic respiration. The results indicated that the relative abundances of five representative aerobic respiration-related genes, cyc (expressing cytochrome c), ccmA (expressing heme exporter protein A), oxyR (expressing hydrogen peroxide-inducible gene activator), ahpC (expressing peroxiredoxin), and sod2 (expressing superoxide dismutase 2) [ 39 ], were significantly increased, while the relative abundances of two representative anaerobic respiration-related genes, nrfA (expressing nitrite reductase) and adh (expressing alcohol dehydrogenase) [ 40 ], were significantly decreased in the flr7 root microbiome compared to the Nip root microbiome ( Fig. 3B ; Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since FLR7 affects rhizosphere oxygen levels, we further analyzed genes related to aerobic and anaerobic respiration. The results indicated that the relative abundances of five representative aerobic respiration-related genes, cyc (expressing cytochrome c), ccmA (expressing heme exporter protein A), oxyR (expressing hydrogen peroxide-inducible gene activator), ahpC (expressing peroxiredoxin), and sod2 (expressing superoxide dismutase 2) [ 39 ], were significantly increased, while the relative abundances of two representative anaerobic respiration-related genes, nrfA (expressing nitrite reductase) and adh (expressing alcohol dehydrogenase) [ 40 ], were significantly decreased in the flr7 root microbiome compared to the Nip root microbiome ( Fig. 3B ; Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…3C ). Aerobic respiration is accompanied by antioxidant reactions that exist in aerobic bacteria but not in anaerobic bacteria [ 39 ]. GO function analysis showed that the relative abundances of multiple antioxidant-related functions were significantly elevated in the mutant root microbiome ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In GAS, the quorum-sensing transcriptional regulator of the speB - prsA operon, RopB/Rgg, is unusually rich (a total of 10) in cysteine residues. Some of these cysteine residues are critical for RopB/Rgg activity and could thus serve as redox switches in oxidative stress sensing to regulate speB expression levels ( 66 69 ), providing a possible explanation for strongly repressed speB promoter activities in the HKU16Δ gshT mutant ( Fig. 3b ).…”
Section: Discussionmentioning
confidence: 99%
“…Responses to ROS evolutionarily range from the activation of transcription factors in prokaryotes to promoting cellular responses (such as cell migration and proliferation) in humans 22,23 . Even cellular outcomes within the same organism can vary depending on ROS levels.…”
Section: Introductionmentioning
confidence: 99%